Purchasing behavior for pirated products: a structural equation modeling approach on Bangladeshi consumers - Rahman, Sabbir; Haque, A. K. M. Ahasanul; Rahman, Mahbubur (South Asia Publications on behalf of Management Science Association, Faculty of Management Studies, University of Delhi, 2011)
The purpose of this study is to explore the factors influencing the Bangladeshi consumers’ perception toward purchasing pirated products. To explore these factors, this study had conducted a survey among the Bangladeshi consumers’. The data analysis was conducted through exploratory factor analysis, confirmatory factor analysis and structural equation modeling to test the hypotheses. Among the four variables, individual personalities and economic conditions are the most significant followed by social influences and pricing of pirated products. The outcome of this research showed a comprehensively integrated framework for policy maker and business enterprise to understand the dynamic relationships among dimensions of social influence, pricing, economy, and personality to understand the consumers’ perception toward purchasing pirated products. Further research is needed to examine these factors with additional samples before generalization can be made.